Photoadaptation to ultraviolet B TL01 in psoriatic patients. (27th April 2020) - Pacifico, A.; Damiani, G.; Iacovelli, P.; Conic, R.R.Z.; Scarabello, A.; Filoni, A.; Malagoli, P.; Bragazzi, N.L.; Pigatto, P.D.M.; Morrone, A.
Abstract: Background: In the biologic era, narrow‐band ultraviolet B (NB‐UVB) phototherapy still remains a valuable, effective, inexpensive, safe anti‐psoriatic treatment. Patients can lose response to NB‐UVB over time due to photoadaptation. This phenomenon is the tendency of the skin to respond to ultraviolet (UV) exposure by undergoing changes that may result in a decreased future response to an equivalent dose of radiation, thus leading to the need for an increased exposure during phototherapy course. Aim: To characterize and quantify the determinants of photoadaptation in NB‐UVB treated psoriatic patients. Methods: We enrolled 57 adult patients with moderate plaque psoriasis. Patients underwent 24 sessions of NB‐UVB phototherapy delivered thrice a week. Dosing was started with 70% of the minimal erythema dose (MED) with percentage‐based dose increments every two treatments. MED as well as change in the erythema and melanin index (MI) were measured at baseline and at the end of phototherapy course. Moreover, an adaptation factor (AF) was calculated for each patient. Results: Adaptation factor was not influenced by both baseline MED and skin type. We found a weak correlation between higher cumulative dosages and the initial MED (Spearman's rho = 0.32, P = 0.0154) as well as with the mean initial MI (Spearman's rho = 0.25, P = 0.0624, statistically borderline). Clearance and mean number of treatments were correlated (Spearman's rho = 0.48, P < 0.001). Conclusion: Photoadaptation is a physiological skin response that negatively influences NB‐UVB responsiveness and is not predictable by the baseline MED and skin type. Thus, starting with more aggressive protocols and increasing rapidly dosage progression to prevent AF may increase NB‐UVB response.